Late Holocene environmental and hydro-climatic variability inferred from a shallow lake record, blowout dunes, Argentinian western Pampas, South America. (June 2022) - Vilanova, Isabel; Tripaldi, Alfonsina; Schittek, Karsten; Rojo, Leandro; Piovano, Eduardo L.; Forman, Steven L.; Jobbágy, Esteban G.; Heider, Guillermo; Chiesa, Jorge
Abstract: The Pampas plains of southern South America were predominantly dry, eolian-shaped landscapes, besides some interposed humid phases, during most of the late Pleistocene-Middle Holocene, evolving to humid-subhumid grasslands hosting an increasingly large number of shallow lakes in the late Holocene. These lakes proved to preserve in their sediments worthy evidence to interpret past environmental-ecological conditions, offering tools to analyze climatic variability and human impacts during the last millennia. This is the case of the shallow lake Primera Laguna, located in the western and driest edge of the Pampas. Here, we present a multiproxy study from this shallow lake with the aims of contributing to reconstruct its past stages, infer the climatic scenarios that drove its evolution, evaluate the potential anthropogenic role in these changes, and correlate/analyze this record with available data from other Pampean lakes. We analyzed a high-resolution palynological record, accompanied by macroscopic charcoal accumulation rates, C/N, C and N stable isotopes, magnetic susceptibility, and sediment geochemistry, of a 41-cm long sediment core, extracted from the deepest sector of the lake. An age-depth model based on AMS chronology indicates a preserved lake history for the past ∼1400 cal yr BP. Ecological and sedimentological interpretations allowed us to propose four main periods during this time lapse. For the first period (1375–1069 cal yr BP, 575–881 CE), the integrative interpretation indicates a very low shallow lake –mostly oligotrophic, alkaline, and clear water–, dominated by the accumulation of epiclastic silty fine sand from the surrounded eolian landscape and covered by xerophytic vegetation. In the second period, between 1069 and 738 cal yr BP (881–1212 CE), we inferred a trend to rising lake levels and mesotrophic conditions, and more pollen taxa than the previous period, and with lake margins dominated by cattails and sedges. The third period (738–193 cal yr BP, 1212–1757 CE) was characterized by more variable and lower lake levels compared to previous periods and more frequent desiccation processes at the lake margins. Then, during the fourth period (last 195 cal yr, 1757–2015 CE), there was a gradual transition towards a larger and more stable shallow lake with a deeper water column, and under a turbid state probably related to eutrophication. From the comparison between Primera Laguna record and the previously studied Nassau shallow lake, located in the same eolian landscape, we found a synchronic evolution, implying common drivers of change in terms of climatic variability and human impact. Correlation with shallow lakes from the more humid belt of the Pampas suggests widespread increases of water availability in the region since ∼1500 cal yr BP, variable/lower lake levels during ∼600–200 cal yr BP, and a shift to positive hydrological balances up to the present highstands. Graphical abstract: Image 1 Highlights: Multi-proxy study of a shallow lake sediment core of western Pampas of Argentina. Combined pollen, charcoal, C–N stable isotope, and geochemistry record with AMS ages. High-resolution reconstruction exposes four main periods for the past ∼1400 cal yr. Main inferred forcing is climatic variability modulated by anthropogenic impact.